Rapid Excavation and Tunneling Conference 2023 Proceedings - Carlson, Jarrett E. (Society for Mining, Metallurgy & Exploration, Incorporated, 2023)
Every two years, industry leaders and practitioners from around the world gather at the Rapid Excavation and Tunneling Conference (RETC) to learn about the most recent advances and breakthroughs in this unique field. This book includes the full text of 133 papers presented at the 2023 conference.
Description based upon print version of record.
Acclimatization: Adapting Conventional Tunnel Lining Techniques to Overstress Rock Conditions
Keywords: elektronické knihy; electronic books